Implementação de aparato experimental para medição de instabilidades tipo Roll Waves em fluidos não- newtonianos - Cunha, Evandro Fernandes da [UNESP] (2013)
This dissertation makes an approach to the experimental work carried out within the research of non-Newtonian fluids drained in inclined channels. When these flows are placed in favorable slope and flow, can be a suitable area to the spread of instability at the free surface which may eventually evolve into a specific type of waves, known in the literature as roll waves. These waves of well- defined length and amplitude are especially affected by the flow characteristics and the fluid. In terms of fluid test was elaborated, rheologically characterized and used carbopol gel, polymer-based and non-Newtonian property, with good adjustment of the rheological model of Herschel-Bulkley. As there is a big gap in the literature regarding to both measures of this phenomenon in nature as in the laboratory, was sought in this work, the formation of an experimental apparatus that was able to reproduce the necessary conditions for the generation of roll waves in the laboratory, under those controlled conditions. Photometric and ultrasonic techniques were used in the experiment for measuring height information of the flow after the test fluid (carbopol gel) being disturbed by a specific system designed for this purpose. The experimental apparatus developed now enables simulations of roll waves in various scenarios for different fluid rheology, is thus an invaluable support to the understanding and control of this roll waves present in mud, for example